RISKS AND Opportunities IN Development OF NEW DRUG - Kummari Paramesh; B, Thejovathi; l, Harikiran (International Journal of Allied Medical Sciences and Clinical Research, 2025)
Drug Regulatory Affairs refers to all aspects within the pharmaceutical process on drug discovery and research which also deals with many risks and opportunities of drug development and they have subject to different degrees of regulations of different countries such as India, USA, Europe. The pharmaceutical law frame is used as guidelines on covering Quality, Safety and Efficacy of a drug as well as Health Authorities’ attitudes and requirements are employed for the correct pathway of pharmaceutical needs and have a great influence on the drug development process and had success through it. The role of Regulatory affairs professionals deals with all these aspects to get a desired result of drug development. The health authorities are framed to guide and analyse the drug which fulfils the appropriate quality and efficacy.